Assessment of the application for renewal of authorisation of Bonvital® (Enterococcus faecium DSM 7134) as a feed additive for weaned piglets and pigs for fattening. (19th March 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Bonvital ® is the trade name for a feed additive based on Enterococcus faecium DSM 7134 currently authorised for use in piglets, pigs for fattening, sows, chickens for fattening, chickens reared for laying and minor poultry species. This opinion concerns the renewal of the authorisation of Bonvital ® as a zootechnical additive for weaned piglets and pigs for fattening. The applicant is proposing to increase the minimum and maximum inclusion level of the additive in feed for weaned piglets and the maximum for pigs for fattening. The applicant has provided data demonstrating that the additive currently in the market complies with the conditions of authorisation. E . faecium DSM 7134 does not belong to the hospital‐associated clade and does not express resistance to the antibiotics tested; therefore, its use in animal nutrition is considered safe for the target animals and consumers of animal products. Bonvital ® is also considered safe for the target animals and consumers. In previous opinions, Bonvital ® was found to be non‐irritant to skin and eyes, but a potential skin/respiratory sensitiser and safe for the environment. No new evidence has been identified that would make the Panel reconsider the previous conclusions on the safety of the additive. The conclusions reached before are considered to cover the higher maximum application rates proposed by the applicant. Therefore, the Panel concludes that Bonvital ® used under the proposed conditions of use is safe for weaned piglets and pigs for fattening, consumers of products derived from animals fed Bonvital ® and the environment. Bonvital ® is considered a potential skin/respiratory sensitiser. The additional studies provided confirm that Bonvital ® has the potential to be efficacious in weaned piglets at 1 × 10 9 colony forming unit (CFU)/kg feed and in pigs for fattening at 2 × 10 8 CFU/kg feed.